Municipal Oligarchies and Manorialisation Practices in Late Medieval Avila (Edad Media. Revista de Historia, 2019)
The objective of this essay is to analyze the different forms taken by the process of irregular manorialisation of the land under royal domain (realengo) in the late Middle Ages. Drawing on the case of the concejo or municipality of Avila, an analysis is carried out of the strategies employed by the local oligarchies in order to weave informal relations of dominance over the aldeas (villages) and their settlers. The link between these irregular manorial forms and the legitimate forms of oligarchical land ownership is particularly emphasized. This analysis aims to stress the significance of dominance relations over the producers as inseparable from the development of privileged landed property.
Keywords: Oligarchy; Manorial Tenure; Concejo; Ávila; Late Middle Ages